2015
DOI: 10.1140/epjc/s10052-015-3467-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of non-canonical scalar field model using various parametrizations of dark energy equation of state

Abstract: In this present work, we try to build up a cosmological model using a non-canonical scalar field within the framework of a spatially flat FRW space-time. In this context, we have considered four different parametrizations of the equation of state parameter of the non-canonical scalar field. Under this scenario, analytical solutions for various cosmological parameters have been found out. It has been found that the deceleration parameter shows a smooth transition from a positive value to some negative value whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 118 publications
5
9
0
Order By: Relevance
“…It is evident from figure 4 that q(z) shows a smooth transition from a decelerated (q > 0) to an accelerated (q < 0) phase of expansion of the universe at the transition redshift z t = 0.7 +0.02 −0.02 (within 1σ errors) and z t = 0.7 +0.05 −0.05 (within 2σ errors) for the best-fit model. This results are found to be consistent with the results obtained independently by several authors (see [67][68][69] and references there in), which states that the universe at redshift in between z t ∼ 0.5 − 1 underwent a phase transition from decelerating to accelerating expansion. Furthermore, we have also reconstructed the EoS parameter ω DE (z) for the dark energy in figure 5.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is evident from figure 4 that q(z) shows a smooth transition from a decelerated (q > 0) to an accelerated (q < 0) phase of expansion of the universe at the transition redshift z t = 0.7 +0.02 −0.02 (within 1σ errors) and z t = 0.7 +0.05 −0.05 (within 2σ errors) for the best-fit model. This results are found to be consistent with the results obtained independently by several authors (see [67][68][69] and references there in), which states that the universe at redshift in between z t ∼ 0.5 − 1 underwent a phase transition from decelerating to accelerating expansion. Furthermore, we have also reconstructed the EoS parameter ω DE (z) for the dark energy in figure 5.…”
Section: Resultssupporting
confidence: 92%
“…This is essential for the structure formation of the universe. In addition, the best-fit value of the transition redshift (z t = 0.7 +0.05 −0.05 , at 2σ level) obtained in this work is found to be consistent with the results obtained independently by several authors [67][68][69]. Furthermore, it has also been found that for the best-fit model, the evolution of ω DE shows a little phantom nature at the present epoch, which is well consistent with the Planck 2015 data [5].…”
Section: Discussionsupporting
confidence: 92%
“…For the best-fit model, the present value of ω φ (z) comes out to be −0.99 +0.04 −0.03 (with 1σ errors) and −0.99 +0.08 −0.07 (with 2σ errors), which is definitely within the constraint range [60,61]. Moreover, our results are also in good agreement with other previous works [38][39][40][41], where the authors have considered different table 2). The 1σ and 2σ confidence regions have been shown and the central dark line represents the best fit curve.…”
Section: Results Of Data Analysissupporting
confidence: 91%
“…In literature, there are many examples where the authors had proposed different redshift parametrizations of ω φ to fit with observational data [34][35][36][37] (for review, see also Refs. [38][39][40][41]). However, it has been found that the parametrization of the energy density ρ φ (z) (which depends on its EoS parameter through an integral) provides tighter constraints than ω φ (z) from the same observational dataset (for details, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the k-essence is one of the simple form of a non-canonical scalar field model. In the present work, we will consider non-canonical scalar field model with general form of k-essence Lagrangian [58,59,60,61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%